PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP MOTIVASI SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN PT. BANK OCBC NISP Tbk CABANG PEKANBARU - Oemar, Yohanas (Jurnal Tepak Manajemen Bisnis, 2015)
The purpose of this study was to determine the effect of leadership on employee motivation at Bank OCBC NISP Tbk Pekanbaru branch. The effect of competence on the motivation of employees at PT. Bank OCBC NISP Tbk Pekanbaru branch. Knowing the influence of leadership on employee performance at PT. Bank OCBC NISP Tbk Pekanbarubranch. Knowing the competencies on the performance of employees at PT. Bank OCBC NISP Tbk Pekanbaru branch. Knowing the influence of motivation on employee performance at PT. Bank OCBC NISP Tbk Pekanbaru branch.In this study, the population is all employees of PT Bank OCBC NISP Tbk Pekanbaru branch as many as 116 people. Stratified sampling random sampling, this the number of samples that will be used is 54 employees. Sampling was done by stratified random sampling method authors grouping based on the division of the existing population in PT Bank OCBC NISP Tbk Branch Pekanbaru.Based on the result of the study of leadership has an influence on motivation at Bank OCBC NISP Tbk Pekanbaru branch. Competencies have an influence on motivation at Bank OCBC NISP Tbk Pekanbaru branch. Leadership has an influence on the performance of the PT. Bank OCBC NISP Tbk Pekanbaru branch. Competence has an influence on the performance of the PT. Bank OCBC NISP Tbk Pekanbaru branch. Competence has an influence on the performance of the PT. Bank OCBC NISP Tbk Pekanbaru branch.Keywords : Leadership, Competencies, Motivation, Employee Performance